Index for Rating Predictive Accuracy of Screening Tests - Choi, B. C. K. (Methods of Information in Medicine, 1982)
This paper proposes a new pair of indices, the »predictive powers«, for measuring the predictive accuracy (predictivity) of screening tests.Sensitivity and specificity are indices for measuring the validity of a test. They give the probability of a certain test result given a substance of known condition (a carcinogen or a non-carcinogen). They do not describe the predictive accuracy of a test, which is the probability of a certain condition (a carcinogen or a non-carcinogen) given a known test result. Predictive values are unsuitable measures for characterizing a test since they are seriously affected by the prevalence of carcinogens. However, the predictive powers do not have this limitation and are shown to be useful indices for the purpose of rating the predictive accuracies of various screening tests.
Keywords: Screening Tests; Predictive Accuracy; Predictive Power